The role of field education officials in the acquisition of teachers of the competencies of teaching science from the viewpoint of students trained in the Faculty of Education; in Shaqra University in Afif - Al-Otaibi, Daidan Nasser (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the role of field education officials (college supervisor, school principal, and collaborating teacher) - the importance and practice of - in students ’teachers acquiring the necessary competencies to teach science. And to identify the problems facing students, from the viewpoint of student teachers in the disciplines of natural sciences, at the Faculty of Education at Shaqra University in Afif, and to achieve the goals of the study, the researcher used the descriptive approach; the tool was a questionnaire that was applied to the entire study population, which was (60) students.The results showed the following: The overall role obtained a total average of (3.36 out of 5) with an important / high verbal grade, and at the level of the two main aspects, the importance aspect obtained a general average (3.43) with a verbal grade (very important), while the degree of practice aspect got an average (3.28) with a grade of (high) and at the level of fields; the practices of the school principals were the most important among field education officials, and the college supervisor was the best practicing of his roles. And that the most important problems facing the student teacher with regard to the college supervisor is the lack of attendance of the classes that the student performs in the school of application.Based on the results of the study, the researcher presented a set of recommendations, including: the necessity of identifying the largest possible number of distinguished schools for field training for students in science teachers; coordination and joint work to clarify the roles of each authority related to field education; and finding appropriate solutions to the problems facing students / teachers. The researcher has suggested a number of studies that can contribute to the advancement of field education in science education.
Keywords: role of education officials; student teacher; field education; competencies; science